Killing Your Neighbors : Friendship and Violence in Northern Kenya and Beyond - Holtzman, Jon (Book collections on Project MUSE., 2017)
"One of the most disturbing spectacles of recent decades has been brutal acts of genocidal violence committed among neighboring communities who once lived together in peace: ethnic cleansing in the former Yugoslavia; the slaughter of Tutsis in Rwanda; or the Sunni versus Shia violence in today's Iraq. As these cases illustrate, lethal violence does not always come at the hands of outsiders or foreigners. Rather, it can just as easily come at the hand of someone who once was considered a friend. Killing Our Neighbors employs a multi-sited approach and multi-vocal ethnography to examine how once-peaceful neighbors become transformed into perpetrators and victims of lethal violence. It engages with a set of interlocking case studies in northern Kenya, focusing on sometimes-peaceful, sometimes violent interactions between Samburu herders and neighboring groups, interweaving Samburu narratives of key violent events with the narratives of neighboring groups on the other side of the same encounters. The book is, on one hand, an ethnography of particular people in a particular place, vividly portraying the complex and confusing dynamics of interethnic violence through the lives, words and intimate experiences of individuals variously involved in and affected by these conflicts. At the same time the book aims to use this particular case study to illustrate how the dynamics in northern Kenya provides comparative insights to well-known, compelling contexts of violence around the globe"--Provided by publisher.